Role of silicone stenting in endoscopic dacryocystorhinostomy - Jahan, Abdussalam M.; Eldanfur, Yousef M.; Ghuzi, Abdulhakim B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Dacryocystorhinostomy (DCR) is a surgical procedure performed to relief nasolacrimal duct obstruction, which involves the creation of ostium at the lacrimal bone to form a shunt in the nasolacrimal pathway. Closure of the rhinostomy opening was considered a major factor for surgical failure. Use of silicone stent in endoscopic DCR to improve the success rate of the operation have been tried by many surgeons. In this study we assess the success rates of endoscopic DCR with and without silicone stents. Methods: Prospective study includes 30 patients were operated in the Department of ENT, Misrata Medical Center, from April 2017 to March 2018. They underwent endonasal endoscopic DCR for primary acquired nasolacrimal duct obstruction. These patients were randomly divided in two groups: A and B with 15 patients in each group. The group A patients underwent endoscopic DCR with silicone stent and group B patients underwent endoscopic DCR without stent. The results were statistically analyzed by chi-square test. Results: 30 patients were included in this study, their age ranged from 17 to 60 years, complaining of epiphora, 24 (80%) were females and 6 (20%) were males. The success rate was higher in patients with silicone stent (93.33%) as compared to patients without silicone stent (86.67%) but this difference in the results is not statistically significant (As p value is 0.542 which is >0.05). Conclusions: Endoscopic DCR is safe, successful procedure for treatment of nasolacrimal duct obstruction and there was no significant difference in the success rates of performing endonasal DCR with silicone or without silicone stents.